Management of Pediatric Traumatic Cataract With An Open Globe Injury - Levandi Mulja; Mayasari Wahyu; Irawati Irfani; Primawita Oktarima (Majalah Oftalmologi Indonesia, 2022)
Introduction: Traumatic cataract is one of the leading causes of monocular blindness in children. The management of pediatric traumatic cataract is challenging; the growing size of the affected eyes and the risk of amblyopia further complicate things. The timing of cataract removal and IOL implantation remain controversial until today. Case Report: A thirteen-years-old boy came with his left eye punctured by a pencil tip. He came in with a visual acuity of 1/300, a full-thickness 5 mm paracentral corneal laceration and traumatic cataract. The patient went through a two-step surgery. Cataract surgery and IOL implantation was conducted one week following corneal laceration suture. Discussion: Two-step surgery was performed on this patient with consideration being cataract removal performed when the inflammation of the eye was subside and also a more accurate IOL calculation. One study stated, even with 43.4% of patient’s anterior capsule ruptures, it would postponed cataract surgery for 2 days up to 6 months. In this case, a week after first surgery, it revealed anterior capsule rupture and the lens material was touching corneal endothelium. Therefore, lensectomy was performed because it touches the corneal endothelium causing further damage Conclusion: The two-step procedure performed was a preferable surgery for a traumatic cataract in a quiet eye, because it has better potential for visual improvement and IOL calculation. However, since the anterior lens capsule ruptured and the lens material prolapsed into the anterior chamber, it would have been even better to perform lensectomy as an early procedure to prevent inflammation.